Biomechanical Analysis of a Custom-Made Mouthguard Reinforced With Different Elastic Modulus Laminates During a Simulated Maxillofacial Trauma - Tribst, Joao Paulo Mendes [UNESP]; Dal Piva, Amanda Maria de Oliveira [UNESP]; Ausiello, Pietro; De Benedictis, Arianna; Bottino, Marco Antonio [UNESP]; Borges, Alexandre Luiz Souto [UNESP] (Sage Publications Inc, 2020)
Background/Aims: There is a lack of data regarding the influence of different laminates for mouthguard reinforcement in the mechanical response during an impact in the orofacial region. The aim of this study was to verify the influence of the laminate framework on the stresses and strains of the anterior teeth and displacement of ethylene-vinyl acetate (EVA) custom-made mouthguards during a simulated impact. The null hypotheses was that the different laminates reinforcement would present the similar effect in maxillary structures, regardless the elastic modulus. Methods: A finite element model of human maxillary central incisors with an antagonist contact was used. A linear quasi-static analysis was used to simulate the force exerted during an impact. A total of 5 different layers were simulated inside the mouthguard at the labial portion according to the Elastic Modulus 1 MPa (Extremely flexible), 9 GPa (Low modulus reinforcement), 18 GPa (Without reinforcement), 50 GPa (Flexible alloy), 100 GPa (Titanium alloy) and 200 GPa (Hard material). The results were evaluated by means of Maximum Principal Stress (in the tooth and bone), Microstrain (periodontal ligament) and Displacement (mouthguard) criteria. Results: The elastic modulus of the material inside the MG influenced the stress distribution on the enamel buccal face. However, it did not affect the bone tissue stress, periodontal ligament strain or root dentin tissue stress. Conclusion: The use of reinforcement inside the custom-made mouthguard can modify the stress generated in the enamel buccal surface without improvement to the root dentin, periodontal ligament or bone tissue.
Keywords: custom mouthguards; maxillofacial trauma; sports dentistry; finite element analysis